Drying kinetics of coarse lignite particles in a fixed bed - Pusat, Saban; Akkoyunlu, Mustafa Tahir; Erdem, Hasan Huseyin; Dagdas, Ahmet (ELSEVIER, 2015)
In this study, experimental works for a Turkish lignite in a fixed bed dryer were carded out Drying experiments were carried out at 70,100 and 130 degrees C drying air temperatures, 0.4, 1.7 and 1.1 m/s drying air velocities, 80, 130 and 150 mm sample heights and 20,35 and 50 mm sample sizes. Suitability of twelve thin-layer drying models in describing the drying kinetics of lignite was evaluated by using statistical analyses. The results show that Wang&Singh model is the best model describing the drying behavior of coarse lignite particles in a fixed bed dryer, which is different from the literature. Additionally, the effects of drying parameters on model coefficients were studied by multiple regression analysis. Finally, apparent diffusion coefficient range was presented. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Lignite; Drying kinetics; Fixed bed; Modeling; Turkey; LOW-RANK COAL; LAYER; TEMPERATURE; MICROWAVE; CHINESE; SIMULATION; ENERGY; DRYER; Chemistry; Energy & Fuels; Engineering